The rite [videorecording (DVD)] - Håfström, Mikael; Hopkins, Anthony, 1937-; O'Donoghue, Colin, 1981-; Jones, Toby, 1966-; Hauer, Rutger, 1944-2019 (Distributed by Warner Home Video, 2011)
Inspired by true events, this supernatural thriller follows a seminary student sent to study exorcism at the Vatican in spite of his own doubts about the controversial practice and even his own faith. Only when sent to apprentice with legendary Father Lucas, who has performed thousand of exorcisms, does his armor of skepticism begin to fall. Drawn into a troubling case that transcends even Father Lucas's skill, the young seminarian glimpses a phenomenon science can't explain or control.